France, 1800-1914 : a Social History. - Magraw, Roger (Social history of Europe., 2014)
Nineteenth-century France was a society of apparent paradoxes. It is famous for periodic and bloody revolutionary upheavals, for class conflict and for religious disputes, yet it was marked by relative demographic stability, gradual urbanisation and modest economic change, class conflict and ongoing religious and cultural tensions. Incorporating much recent research, Roger Magraw draws both upon still-valuable insights derived from the 'new social history' of the 1960s and upon more recent approaches suggested by gender history, cultural anthropology and the 'linguistic turn'.